NANOMICELLAR DISPERSION-BASED APPROACH TO IMPROVE AMISULPRIDE DISSOLUTION: FORMULATION, CHARACTERIZATION, AND IN VITRO RELEASE STUDY - HASHIM, HAIDER HANI; JABER, SABA ABDULHADI (International Journal of Applied Pharmaceutics, 2025)
Objective: This research aims to overcome the solubility and absorption limitations of amisulpride (AMS) by formulating it into a nano-micellar (NM) delivery system, thereby improving its oral bioavailability and efficacy as an antiemetic through enhanced dissolution rate and extent. Methods: Six types of nanocarriers, Soluplus(SLP), D-α-tocopheryl polyethylene glycol 1000 succinate(TGPS), Poloxamer (POL 188 and407), Solutol HS-15(STL-H15), and Tween-80, were used for the preparation of AMS as nano micellar dispersion(AMS-NM) either alone with 1:2,1:4,1:6, and 1:8 ratios or in combination with 1:4:1 and 1:4:2 ratios by utilizing Thin film hydration method. Twenty-four formulas were prepared and primarily checked for physical stability, then subjected to particle size (P. size), polydispersity index (PDI), entrapment efficiency (EE%), drug loading (DL%), and solubility factor (Sf) measurements. Only the selected formulas with accepted results of physical appearance and in vitro Characterization will progress to the release Study. Morphological and compatibility analyses, as well as Differential Scanning Calorimetry (DSC) and X-ray diffraction, were performed only for one optimal formula. Results: Out of 24 nanomicelle formulations (F1–F24), four (F2, F4, F6, and F18) exhibited physical stability with optimal P. size, PDI, EE%, and Sf, qualifying them for further release studies. The formulation F2, containing a 1:4 ratio of SLP, emerged as the optimized system, achieving a complete (100%) release of AMS within 45 min, significantly surpassing the 24% release observed from the pure drug suspension. F2 demonstrated a nanoscale p. size of 67.1±2.2 nm, low PDI (0.061±0.002), high EE% (73±3.6), drug loading of 14.6±0.09%, and a solubility factor of 4.3. It presented a clear, faint light blue appearance with nano-spherical morphology, excellent drug-excipient compatibility, and structural stability. DSC and PXRD analyses confirmed successful AMS entrapment within the micellar core. Conclusion: This strategy not only addresses AMS’s inherent solubility limitations but also utilizes nanoscale carrier properties and size-dependent mechanisms to enhance drug dissolution and absorption, thereby optimizing therapeutic delivery and showing great promise for improving clinical efficacy.